COMPARATIVE ANALYSIS OF IPO PROCESSES IN EMERGING MARKETS (British Journal of Global Ecology and Sustainable Development, 2026)
The article is devoted to a comparative analysis of the theoretical and practical aspects of the processes of initial public offering (IPO) in emerging markets. The study revealed the differences in the mechanisms of IPOs of developed and developing countries in terms of the institutional environment, legal regulation, information transparency, corporate governance, and investor behavior. Based on a comparative analysis, the main factors limiting the effectiveness of IPOs in emerging markets are substantiated, including underpricing, insufficient investor confidence, and weak regulatory mechanisms. The research results will serve to develop scientific conclusions and practical proposals aimed at forming a national IPO model in developing countries, deepening capital markets, and improving the investment climate.